Consumptive Behavior in the Digital Era: A Literature Study on Generation Z and Millennials in E- Commerce - Yusma Amrulloh Tri Firmansyah; Fery Setiawan (West Science Business and Management, 2025)
This research aims to examine the consumptive behavior of Generation Z and Millennials in the use of E-Commerce in the digital era. The writing method uses a review of literature articles obtained through the Science and Technology Index (SINTA) Journal and Copernicus. The results show that in using e-commerce, Gen Z and Millennials show high interest in promotional elements such as competitive prices, attractive discounts, and flash sale programs. However, there are differences in preferences that reflect the characteristics of each generation.